Do Macroeconomic Effects of Capital Controls Vary by their Type? : Evidence From Malaysia - Tamirisa, Natalia (Washington, D.C. : International Monetary Fund, 2004)
This paper examines how the macroeconomic effects of capital controls vary depending on which type of international financial transaction they cover. Drawing on Malaysia's experiences in regulating the capital account during the 1990s, it finds, in an error-correction model, that capital controls generally have statistically insignificant effects on the exchange rate. Controls on portfolio outflows and on bank and foreign exchange operations facilitate reductions in the domestic interest rate, while controls on portfolio inflows have the opposite effect, in line with the theoretical priors. Controls on international transactions in the domestic currency and stock market operations have statistically insignificant effects on the interest rate differential.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet